2009
DOI: 10.1027/0269-8803.23.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Neurophysiological Markers of Inhibitory and Temporal Processing Deficits in Children and Adults with ADHD

Abstract: We compared ADHD-related temporal processing and response inhibition deficits in children and adults using event-related potentials (ERPs) during cued continuous performance tasks (CPT, O-X-version, plus a more demanding flanker version). ERP markers of temporal processing (Cue CNV) and inhibition (NoGo P300) were obtained in matched groups of children (32 with ADHD, mean age 11.2 years, and 31 controls, mean age 11.1 years) and adults (22 ADHD, mean age 42.7 years, and 22 controls, mean age 44.0 years). ERP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 40 publications
(58 reference statements)
9
83
2
Order By: Relevance
“…In a CPT study focussing on motor response execution and inhibition, intact N2 but attenuated P3b in AD/HDcom was taken to indicate a lower degree of controlled stimulus processing during response inhibition (Banaschewski et al, 2004). Children with ADHDcom have been reported to have problems with response preparation as indicated by the CNV to cue stimuli, and deficient response inhibition as indicated by Nogo-P3 (Valko et al, 2009). As outlined in the attention section, during a CPT task young children with ADHD characteristics did not show differences in ERP components related to conflict (Nogo N2) or inhibition (Nogo P3) processing (Spronk et al, 2008;see Table 1).…”
Section: Go/nogo and Cptmentioning
confidence: 99%
“…In a CPT study focussing on motor response execution and inhibition, intact N2 but attenuated P3b in AD/HDcom was taken to indicate a lower degree of controlled stimulus processing during response inhibition (Banaschewski et al, 2004). Children with ADHDcom have been reported to have problems with response preparation as indicated by the CNV to cue stimuli, and deficient response inhibition as indicated by Nogo-P3 (Valko et al, 2009). As outlined in the attention section, during a CPT task young children with ADHD characteristics did not show differences in ERP components related to conflict (Nogo N2) or inhibition (Nogo P3) processing (Spronk et al, 2008;see Table 1).…”
Section: Go/nogo and Cptmentioning
confidence: 99%
“…However, the exact contributions of the respectively engaged internal processes-which might be the source(s) of the overt RT slowing-are not specified unequivocally (4,7,10,(13)(14)(15)(16)(17). Candidate processing levels are early sensory processes that guide the deployment of focal attention (4,10,22), stimulus-response translation processes that decide upon the correct motor response, and motor-response production processes (5,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 96%
“…To assess preparation and response control and the impact of attentional load thereon, the Standard-CPT as well as a CPT Flanker version (Flanker-CPT) incorporating additional incompatible stimuli were used (Doehnert et al 2008(Doehnert et al , 2010Valko et al 2009). On each trial of both CPT versions, a bold letter was presented for 150 ms subtending 0.6x viewing angle horizontally and 0.8x vertically at 120 cm viewing distance against a light grey background in the centre of a 17-inch (43 cm) cathode ray tube monitor.…”
Section: Stimuli and Taskmentioning
confidence: 99%
“…Clearly, these aspects are interrelated, and thus the NoGo-P3 may be generated by several processes of terminal inhibitory response control in the medial or anterior cingulate cortex, premotor areas and frontal areas (Kiefer et al 1998 ;Strik et al 1998 ;Weisbrod et al 2000 ;Fallgatter et al 2002 ;Verleger et al 2006 ;Beste et al 2008). Clinical studies have shown that the NoGo-P3 is altered in amplitude or anteriorization in patients with ADHD, and represents a persistent neurophysiological deficit (Brandeis et al 2002 ;Fallgatter et al 2004Fallgatter et al , 2005Valko et al 2009 ;Dhar et al 2010 ;Doehnert et al 2010).…”
Section: Introductionmentioning
confidence: 99%